Nutritional and functional properties of underutilized shellfish (molluscs), limpet (Patella vulgata) - Mas Munira Rambli; Eng-Tong Phuah; Nazlin K. Howell (Scientific Reports)
Abstract Limpet, Patella vulgata is an underutilized gastropod mollusc. In this study, the nutritional and techno-functional properties of limpets, found attached to rocks on the shores of Cornwall, Wales and Scotland were explored for the first time. P. vulgata flesh had a high percentage of protein (15%) with a well-balanced amino acid composition. Fat content was about 3%, comprising saturated fatty acids (SFAs), monounsaturated fatty acids (MUFAs) and polyunsaturated fatty acids (PUFAs) in the ratio of 1:1:2. SDS-PAGE characterisation showed the main myofibrillar and sarcoplasmic protein bands from limpet flesh. More importantly, our study showed that limpet had good gelling properties with a high elastic modulus (Gʹ) of 50.79 kPa and a low gelation temperature of 55.7oC. The limpet protein can therefore be used in a food system together with tapioca starch (TS) and whey protein isolate (WPI) to improve the gel texture via various interactions with other components in the food model systems. Our study highlighted that the addition of limpet protein improved the rheological properties and gel strength of the TS and WPI-based composite gel. The present study clearly indicated that limpet, an underutilized shellfish source can benefit the food industry to make novel products and provide alternative diets such as meat free food.